Otimização de torres autoportantes de aço para linhas de transmissão utilizando algoritmos genéticos - Pedro Henrique Rocha de Menezes Braga (2022)
Steel latticed towers are widely used as supports to conductors on transmission lines. On such projects, it is usual to use the same structural solution repeatedly along the line, what allows to achieve significant cost reduction due to structure’s design optimization. This work proposes the development of an optimization methodology based on the Genetic Algorithms concept to reduce self-supporting tower’s self-weight through the variation of its body base and top dimensions. To execute the algorithm, it was necessary to implement a system composed of modules for geometric parameterization, determination of loads, structural analysis, and sizing accordingly to ASCE 10-15. A 25-bar truss benchmark was optimized, and the results showed that the proposed methodology is effective. Besides, the performance of the methodology to optimize a self-supporting 525 kV cat-face tower was evaluated. The comparison of the results with the project of an equivalent tower which is in operation in Brazil proved the effectiveness of the proposed methodology for self-supporting towers optimization.